ANALISIS CACAT PEKERJAAN BETON VERTIKAL PADA PROYEK PEMBANGUNAN LOUVIN APARTMENT MENGGUNAKAN KERANGKA DMAIC - Fulli Fauza Addini, Zahra
Louvin Apartment project is a residential building construction project located in Sumedang, Jawa Barat. According to inspection result in June and July 2020, there are defects that occur after some works is finisihed. The project aims to minimize waste caused by repairing defect work, but quite contrary, repair is the main solution that is done to fix the defect, instead of solving the root causes of the defect. If the root causes are not going to be eliminated, the defect will occur and may cause increase in repair and rework that will result in project loss. This research aims to improve quality of project works result by generating solutions to overcome the root causes of the defect. The research is conducted using define, measure, analyze, improve, and control framework. In the define stage, scope of the problem, process map, and types of defect are defined. The scope of the problem is vertical concrete works that produce column and wall. The identified defects are uneven joint, porous, uneven corner of column and wall, uneven surface, and bleeding. In the measure stage, measurement of quality performance is conducted by calculating sigma level. In the analyze stage, identification of defect root causes and prioritization of sub factors are conducted through failure mode and effect analysis. In the improve stage, solution alternatives were generated and designed for each sub factors priority by analyzing improvement opportunity based on existing condition. In the control stage, control plans are developed in order to ensure that the proposed solution is implemented and contribute to minimize the defect. The resulted sigma level is 3,07, means that the performance is still lagged from the industry standard and needs to be improved. There are 21 defect sub factors and 10 of them are prioritized to be solved. Solution alternatives generated to solve the sub factors are concrete work procedure refinement, inspection form refinement, material management improvement, equipment maintenance mechanism, training evaluation mechanism, supervision system improvement, and procedure of working while raining.